2021
DOI: 10.1039/d0py01480j
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient bionic self-healing flexible waterborne polyurethane elastic film based on a cyclodextrin–ferrocene host–guest interaction

Abstract: Flexible WPU elastic films with superior self-healing based on synergic effects between host–guest interactions and hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…It is found that the peaks of Fc groups are distinctly correlated to the cavity proton peaks of β-CD moieties, showing the obvious cross peaks. This result demonstrates that the Fc units are orthogonally threaded into the β-CD cavity via host–guest interactions. …”
Section: Resultsmentioning
confidence: 83%
“…It is found that the peaks of Fc groups are distinctly correlated to the cavity proton peaks of β-CD moieties, showing the obvious cross peaks. This result demonstrates that the Fc units are orthogonally threaded into the β-CD cavity via host–guest interactions. …”
Section: Resultsmentioning
confidence: 83%
“…As for polyurethane, the introduction of host-guest interactions also contributes to the self-healing capability of polyurethane materials. Zhang et al [24] reported that they produced a series of new selfhealing waterborne polyurethane materials modified with methylated β-cyclodextrin and specially presynthesized ferrocene-diol. When damaged, they can show great self-healing capability of 100 % (slightly damaged) or 98.54 % (severely damaged) repair effect at most.…”
Section: Host-guest Interactionsmentioning
confidence: 99%
“…Figure 4. The cooperative effect between host-guest interaction and H-bonding contributes to the selfhealing capability[24]. Sugane et al[25] reported that they obtained host-guest (cyclodextrin and adamantane) driving selfhealing thermoset polyurethane network films.…”
mentioning
confidence: 99%
“…As so far we know, waterborne polyurethane, consisting of hydrophobic backbone and emulsifier (2, 2-bis(hydroxymethyl)propionic acid, DMPA), had good biocompatibility and high mechanical properties, it could be used as a polymer reinforcement. [15][16][17][18] Besides, what most people do not notice was that its molecular chain contains a large number of carboxyl anions similar to cellulose nanofiber, the latter had been reported to enhance ion conductivity by promoting counterion migration. [19] Therefore, we hoped that PU could be used to simultaneously promote the mechanical strength and ionic conductivity of hydrogel.…”
Section: Introductionmentioning
confidence: 99%